Electrical, optical and theoretical characterization of doped and undoped calamitic liquid crystal: (s)-5-octyloxy-2-[[[4-(2-methyl butoxy) phenyl] imino] methyl] phenol - Serin, M.; Kuruoglu, F.; Mogulkoc, M.; Caliskan, M.; Yalcin-Gurkan, Y.; Yasa-Sahin, O.; Sakar, D.; Bilgin-Eran, B. (NATL INST OPTOELECTRONICS, 2014)
The electrical conductivities of undoped and doped calamitic liquid crystalline compound, (S)-5-octyloxy-2-[[[4-(2-methylbutoxy) phenyl] imino] methyl] phenol (OMPIMP) with tetrabutylammonium tetrafluoroborate as dopant were determined as a function of temperature. Optical studies of undoped and doped OMPIMP thin films were also carried out using spectrophotometer. Optical band gaps of doped and undoped OMPIMP thin films were determined through absorption spectra using Tauc plot. The frontier orbital energies; E-HOMO, E-LUMO and the band gap energies were calculated from the DFT calculations which were carried out by the hybrid B3LYP functional.
Keywords: Calamitic liquid crystals; Electrical conductivity; Phase transition temperature; Optical band gap energy; Density functional theory; MOLECULES; FRAGMENTS; BEHAVIOR; IMINE; ROD; Materials Science; Optics